Behavioural Accounting Explained through Different Factors - Basma Ben Nefissa; Faouzi Jilani Jilani (Indonesian Management and Accounting Research, 2021)
The positive theory of accounting initiated by Watts and Zinmerman in 1978 postulates that the purpose of accounting is to describe, explain and predict accounting facts. The major contribution of this theory is to analyze the effect of accounting output on the main recipients of financial statements. However, in spite of its notable contributions, the positive theory of accounting falls short of studying the context in which the decision-making process by agents takes place s. It has been proved that this context conditions the decision-making process. Numerous studies have therefore been interested in the characteristics of the environment, which include both, organizational factors and individual factors that would condition decisions. It is from this perspective that behavioural accounting, a branch of accounting defined by Hofsted and Kinard (1970) as the analysis of the attitudes of accountants andparticularly non-accountants under the prism of the impact of accounting andparticularly accounting reports, has been developed. Thus, in many fields, both accounting and non-accounting, researchers have felt the need to take a closer look at the behavioural dimension, mainly theemotional and cognitive dimensions of decision-makers, particularly executives, because these dimensions have a significant influence on the decision-making process.In the first part of our article, we will therefore show how the development of behavioral research has taken place in many fields. The aim is to prove that man is not a machine and that man’s specificities, both cognitive and emotional, must be rigorously analyzed to avoid unexpected results .Subsequently, we present a more or less diverse range of work on behavioral accounting . Finally, we prove through a careful and rigorous review of the accounting literature that behavioral accounting offers the opportunity for researchers, particularly practitioners, to be apprehended and thus evaluated through different faculties.